The university professor in the era of globalization - Parra-Escobar, Néstor Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Mr. Rector, professors and friendly professors: Speaking before such a select audience is an honor and a commitment that is largely a challenge, at least for me. It is also an exceptional occasion to return to a subject that has occupied my attention in the field of higher education: the university professor. However, I prefer to start with my observations as a university student in courses for seniors during the last three years, which has allowed me to verify the high training and quality of professional teachers, the development of research, social projection programs, the wide range In terms of physical and technological resources, the new methods of networking, as well as vestiges of teaching methodologies that were already surpassed, clearly show the ancestral resistance of some professors to change their vertically sovereign attitude towards students.